Optimizing Students' Self-Confidence Through Inquiry Learning Model In Class Ii SDN 102052 Chart Kuala Tanjung Beringin District, Serdang Bedagai District - Amelia Syakinah sihombing; Linda SARI; Rizky FADHILAH (RADINKA JAYA UTAMA PUBLISHER, 2023)
Confidence is an important indicator that every individual must have in their daily activities. A student in achieving success in the process of learning activities, must have self-confidence. However, not all students have the same level of confidence in the process of learning activities. The discussion in this research is optimizing students' self-confidence in the process of learning activities through the inquiry learning model. The sample of this study was class II students at SDN 102052 Bagan Kuala, Tanjung Beringin sub-district, Serdang Bedagai district. The research method used is classroom action research (CAR). The results of the research that has been done show an increase in students' self-confidence in the process of learning activities in class when applying the inquiry learning method.